Need to Move to Paperless Examinations - Haque, Anwar Ul (International Journal of Pathology, 2018)
Examinations constitute fundamental integrated element of education and training programs. They not only measure the competency of the candidates but also serve as potent stimulant for better training and learning. If they are defective they may produce catastrophic results. Traditional paper examinations have several serious problems that had led to their replacement with paperless examinations in many developed countries. US examinations for example Step 1, 2 (Ex ECFMG paper exams) are in vogue for some years. Thousands of medical graduates take these examinations across the world to qualify to enter in accredited residency programs in USA. Time has proven their validity.